Effect of polymer composition on the physiochemical properties of microencapsulated fish oil using spray drying - Sarker, Md. Zaidul Islam; F.T., Karim; M.B., Awang; Abu Bakar, Mohd Rushdi; A. K., Azad; Sahena, Ferdosh (2018)
Fish oil are considered as a good source of omega-3 polyunsaturated fatty acids (PUFAs) which have been shown to reduce the risk of coronary heart disease, hypertension, thrombosis, inflammations, rheumatoid arthritis, symptoms of allergies (atopic eczema), some types of cancer and the rate of ageing, and promote the development and functions of central nervous system. In the current study, HPMC 15 cP and HPMC 5 cP were chosen with different concentration as a carrier material.